Anti-hyperglycemic contours of Madhugrit are robustly translated in the Caenorhabditis elegans model of lipid accumulation by regulating oxidative stress and inflammatory response - Balkrishna, Acharya; Gohel, Vivek; Pathak, Nishit; Tomer, Meenu; Rawat, Malini; Dev, Rishabh; Varshney, Anurag (Frontiers in Endocrinology, 2022)
Background The prevalence of diabetes has considerably increased in recent years. In the long run, use of dual therapy of anti-diabetic agents becomes mandatory to attain euglycemia. Also, the incidences of diabetes-related co-morbidities have warranted the search for new therapeutic approaches for the management of the disease. Traditional herbo-mineral, anti-diabetic agents like Madhugrit are often prescribed to mitigate diabetes and related complications. The present study aimed to thoroughly characterize the pharmacological applications of Madhugrit. Methods Phytometabolite characterization of Madhugrit was performed by ultra-high performance liquid chromatography. Evaluation of cell viability, α-amylase inhibition, glucose uptake, inflammation, and wound healing was performed by in vitro model systems using AR42J, L6, THP1, HaCaT cells, and reporter cell lines namely NF-κB, TNF-α, and IL-1β. The formation of advanced glycation end products was determined by cell-free assay. In addition, the therapeutic potential of Madhugrit was also analyzed in the in vivo Caenorhabditis elegans model system. Parameters like brood size, % curling, glucose and triglyceride accumulation, lipid deposition, ROS generation, and lipid peroxidation were determined under hyperglycemic conditions induced by the addition of supraphysiological glucose levels. Results Madhugrit treatment significantly reduced the α-amylase release, enhanced glucose uptake, decreased AGEs formation, reduced differentiation of monocyte to macrophage, lowered the pro-inflammatory cytokine release, and enhanced wound healing in the in vitro hyperglycemic (glucose; 25 mM) conditions. In C. elegans stimulated with 100 mM glucose, Madhugrit (30 µg/ml) treatment normalized brood size, reduced curling behavior, decreased accumulation of glucose, triglycerides, and lowered oxidative stress. Conclusions Madhugrit showed multimodal approaches in combating hyperglycemia and related complications due to the presence of anti-diabetic, anti-inflammatory, anti-oxidant, wound healing, and lipid-lowering phytoconstituents in its arsenal. The study warrants the translational use of Madhugrit as an effective medicine for diabetes and associated co-morbidities.